2010
DOI: 10.1002/pi.2793
|View full text |Cite
|
Sign up to set email alerts
|

Barrier properties of poly(lactic acid) and its morphological changes induced by aroma compound sorption

Abstract: properties of poly(lactic acid) and its morphological changes induced by aroma compound sorption. Polymer International, Wiley, 2010Wiley, , 59 (6), pp.818-826. 10.1002Wiley, /pi.2793 Barrier properties of poly(lactic acid) and its morphological changes induced by aroma compound sorption Gael Colomines, a Violette Ducruet, b Cécile Courgneau, b Alain Guinault a and Sandra Domenek b * The barrier properties of poly(lactic acid) (PLA) play a key role in food packaging applications. For their optimization, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 48 publications
14
86
1
Order By: Relevance
“…Neat PLA oxygen barrier properties are in accordance with published data [54,[60][61][62][63][64][65]. Interestingly, the inclusion of at least 10 wt% of lignin yielded a decrease in oxygen permeability of around 20 %.…”
Section: Composite Materials Characteristicssupporting
confidence: 77%
“…Neat PLA oxygen barrier properties are in accordance with published data [54,[60][61][62][63][64][65]. Interestingly, the inclusion of at least 10 wt% of lignin yielded a decrease in oxygen permeability of around 20 %.…”
Section: Composite Materials Characteristicssupporting
confidence: 77%
“…17 On the other hand, Colomines et al reported that crystallinity had no effect on the O 2 barrier property of PLA. 18 Some authors have suggested that the barrier properties are dependent on the polymorphic structure of PLA due to differences of molecular packing between  and  crystalline forms. 19 This result is supported by the PALS observations of Del Rio et al in which a dedensification of the amorphous phase is identified mainly during  crystallization due to RAF creation.…”
Section: Introductionmentioning
confidence: 99%
“…Block-copolymers can be produced by reactive extrusion of the polymers with peroxides, as done for PLA/PBAT, PLA/PBS and PLA/PCL blends. [72][73][74] To alter the live-time of generated radicals and therefore alter the possibility of diffusion, so-called 'vector-fluids' were used. 66 Additionally, 'surfactants' based on ambipolar molecules with a miscible polar component were used.…”
Section: Part IImentioning
confidence: 99%